2004
DOI: 10.1081/ese-120039377
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Phenol by AcclimatizedPseudomonas putidaCells Using Glucose as an Added Growth Substrate

Abstract: Biodegradation of phenol, a pollutant derived from many industrial processes, was achieved through acclimatized Pseudomonas putida cells. The strategy to overcome the inhibitory effect of phenol on microbial growth involved the addition of glucose, a conventional carbon source. A factorial experimental design was employed in order to optimize the initial phenol and glucose concentrations. The optimum conditions found were applied in 2-lt bioreactors. The development of acclimatized cells and the use of glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…For pollution abatement, these organic compounds are generally removed through physico-chemical methods. These Conventional chemical or physical technologies have inherent drawbacks due to high operating cost, difficulty in operation and production of secondary pollutants [4]. Biodegradation involving the use of naturally occurring microorganisms presents an alternative, yet better approach for the degradation of PAH [5].…”
Section: Introductionmentioning
confidence: 99%
“…For pollution abatement, these organic compounds are generally removed through physico-chemical methods. These Conventional chemical or physical technologies have inherent drawbacks due to high operating cost, difficulty in operation and production of secondary pollutants [4]. Biodegradation involving the use of naturally occurring microorganisms presents an alternative, yet better approach for the degradation of PAH [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported that bacteria continuously exposed in xenobiotic compounds have improved their degradation abilities [19,20]. In microbial communities, a natural selection between microbial species takes place due to pollution.…”
Section: Introductionmentioning
confidence: 99%
“…For environmental applications, the addition of organic substrates, such as glucose, yeast extract, and sodium glutamate has been considered a promising method to substantially enhance the degradation rate of pollutants 30. It has been reported that glucose supplement accelerated phenol degradation in an anaerobic reactor 17.…”
Section: Resultsmentioning
confidence: 99%